UPDATED STANDARDIZED CATCH RATES FOR THE NORTH ATLANTIC STOCK OF SWORDFISH (Xiphias gladius) FROM THE SPANISH SURFACE LONGLINE FLEET FOR THE PERIOD 1986-2019 - Ramos-Cartelle, Ana; Fernández-Costa, José; García-Cortés, Blanca; Mejuto-García, Jaime (2021)
Log-normal Generalized Linear Models (GLM) were used to update the standardized catch rates (in weight and in number) of the Spanish surface longline fleet targeting swordfish during the period 1986-2019 in areas of the North Atlantic stock. Factors such as area, quarter, gear and bait as well as the fishing-targeting strategy - based on the ratio between the two most prevalent species and those most highly valued by skippers - were considered. The base case models explained 59% and 57% of CPUE variability in weight and in number of fish, respectively. The increases in relative abundance in number of fish and in weight between the lowest levels in record occurred during the mid nineties and the values reached in the last year considered in the present analyse were around +65%.